Impact Of Taxation On The Performance Of Small And Medium Enterprises In Aba, Abia State, Nigeria - Agu, Agu Godswill; Onwuka, Onwka Okwara; Aruomah, Obinwanne (Archives of Business Research, 2019)
This work aims at assessing the effect of taxation on the performance of SMEs in Aba Abia State. A survey approach was adopted while the questionnaire was used as an instrument. A randomly selected 162 employees and owners of 40 SMEs were used for the study. Collected data were analyzed using the multiple regression analysis and one sample t-test. Results indicate that significant and positive relationship exist between taxation and the performance of SMEs and that tax assessment, tax collection and tax utilization significantly influence the performance of SMEs in Aba. It was recommended among others that the Nigerian tax system must seek to protect and promote the SMEs for them to contribute meaningfully to economic growth and that they should identify the agents responsible for illegal, multiple tax collections that seek to frustrate SMEs and deal with them accordingly.